Nuclear-Charge Screening in Positronium Formation from Helium Atoms - E. Ghanbari-Adivi (Journal of Sciences, Islamic Republic of Iran)
An analytical treatment of the electron screening effect within an active-electron model is given for positronium formation from helium atoms. A first-order distorted wave approximation with correct boundary conditions is applied to evaluate the transition amplitude. In the range of impact energy for which the introduced perturbative approach is valid, both the total and differential cross sections are calculated and the results for total cross sections are compared with the other calculations and with the available experimental data.